The challenges of family law in the 21st century (essay) - De Valdivia Cano, Ramiro (2011)
Marriage and family are natural and fundamental institutions that are constantly being eroded and threatened to be dissolved due to the enactment of positive norms that facilitate at-fault divorce which are, in essence, anticonstitutional. In the light of Natural Law, International Law and the Catholic Scholar doctrine, this essay interprets the legal and social problems derived from the constant attacks on family and marriage by the political community. Furthermore, it beckons the search for instruments protective of man’s dignity and freedom, in the face of the arrogance of the social forces and the potential arbitrarities of power. It also establishes the need to confer an institutional character to marriage, basing it on a public, social and legally recognized act; and proposes that society as a whole, is responsible for the care and promotion of the family.